Relationship Between Insomnia Severity and Primary Headache Complaints Among Medical Students of UMM - Risma Karlina Prabawati; Atika Salsabila (Universitas Muhammadiyah Malang, 2024)
Background: Primary headaches and sleep disorders such as insomnia are two health complaints that often occur in society, and influence each other. Medical students are a group that is susceptible to sleep disorders such as insomnia and headaches. This can occur because there are other factors such as stress related to academic pressure, assignments, exams and lack of sleep after activities that cause fatigue and anxiety. Objective: The aim of this study was to determine the relationship between insomnia and primary headache complaints in UMM Medical Faculty students. Methods: This study used an analytical observational method with a cross-sectional approach with the aim of assessing the relationship between insomnia and primary headache complaints in UMM Medical Faculty students. The number of samples in this study was 60 respondents. Data collection used a questionnaire that was asked directly to respondents. Data processing used the SPSS (Statistical Program for Social Science) application. Result: The results of 60 subjects, obtained, respondents with early and moderate insomnia experienced more primary headaches, respectively 25% (15 people) and 15% (9 people). In contrast, respondents without insomnia were more likely to not experience primary headaches, namely 12 people (20%). The results of the Chi-Square test showed a P value of 0.026 <0.05, which means there is a significant relationship between the level of insomnia and primary headaches complaints among UMM FK students. Conclusion: There is a significant relationship between insomnia and primary headache complaints in UMM Medical Faculty students.